Tinjauan Pustaka Retinal Detachment Pada Pediatri - Fadlia Rahmani, Nur (CV RIFAINSTITUT, 2022)
photons then used as electrical and chemical signals for the brain to see visual images.A condition when the neurosensory retina loses attachment to the retinal pigment epithelium (RPE) is referred to as retinal detachment or retinal detachment that can result in degeneration of photoreceptors and ischemia that can cause permanent vision loss.It generally occurs in old age, but can also occur in children with a prevalence of about 0.5-8% of all retinal detachment.Retinal detachment can be classified into three, namely, rhegmatogenous retinal detachment, tractional retinal detachment and exudative retinal detachment.The procedure that can be done in the form of surgery and non-surgery, where surgery is generally done on retina regmatogeno and traction.While in the exudative retinal ablation can be done without surgery.